miR-9-5p Mediates ABCC1 to Elevate the Sensitivity of Glioma Cells to Temozolomide - Chen, Xiang-Rui; Zhang, Yan-Guo; Wang, Qiang (Frontiers in Oncology, 2021)
Chemotherapy combined with surgery is an important clinical treatment for glioma, but endogenous or acquired temozolomide (TMZ) resistance can lead to poor prognosis. microRNA (miR)-9-5p acts in biological function of glioma, but the drug resistance of miR-9-5p in glioma is under exploration. The study intended to test the molecular mechanism of miR-9-5p in glioma cells. MTT assay was applied to investigate the chemosensitivity enhancement of miR-9-5p on TMZ in glioma cells U87-TMZ and U251-TMZ, and in vivo experiments confirmed its role on tumor growth in nude mice. The results of double luciferase reporter gene assay, qRT-PCR and WB indicated that miR-9-5p directly targeted ABCC1 (ATP binding cassette subfamily C member 1) to reduce its expressions. MTT and flow cytometry indicated that elevation of miR-9-5p or down-regulation of ABCC1 could inhibit proliferation-induced apoptosis of drug-resistant cells, and the decrease of miR-9-5p could reverse the reduction of ABCC1 on proliferation-induced apoptosis of drug-resistant cells. In vivo experiments showed that miR-9-5p could promote the anti-tumor role of TMZ. To sum up, the increase of miR-9-5p directly targets ABCC1 and may make glioma cells sensitive to TMZ.